Beyond the Brain: The Peripheral Revolution in Neurodegenerative Diseases - Jahan, Sarwat; Ikram, Muhammad; Khan, Zeeshan (International Journal of Pathology, 2026)
Neurodegenerative disorders were considered diseases limited to the brain. However, the growing evidence clearly indicates that these are the diseases affecting the whole body due to the complex interplay of the brain with the peripheral organs. Recently published data stress the role of the gut microbiota, liver, kidneys, immune system, and vasculature in controlling neuroinflammation, protein misfolding, and neurodegeneration. This is a significant shift from the brain-focused approach and can explain why most of the neuroprotective strategies developed so far failed to show their clinical effectiveness. This editorial aims to present the discussion on how the systems biology perspective should be applied to better understand the disease pathogenesis and translational implications. Multi-omics, artificial intelligence, and precision medicine will open the way to the development of biomarkers and therapies personalized for every patient.